Clima Laboral en el Departamento Administrativo De CONAGOPARE - Zambrano Torres, Iris Renela (2018)
Companies, whether public or private, consider that the work environment is the human and physical environment in which daily work is carried out. Which is affected with leadership style, motivation, decision making, the types of predominant communications and also the setting of objectives within the work system. Therefore, the work environment not only results in the satisfaction of the workers, but they feel committed to their work environment.